Professional Quality of Life and Mental Health among Doctors in Tamil Nadu during COVID19 Pandemic - Mallika, M C Vasantha; Glannie, A R; Venis, Pretty (Indian Journal of Community Health, 2022)
Background: The pandemic COVID19, a serious global threat has led to elevated levels of pressure on medical professionals. The research shows that occupational stressors has been significantly associated with the pandemic.Objective: To estimate the professional quality of life of doctors in Tamil Nadu and their mental health during the COVID19 pandemic. Settings andDesign: Cross-sectional study in Tamil Nadu, South India. Method: Among 318 doctors from both private and government sectors in Tamil Nadu, South India during April 9th - May 10th 2021, the study was conducted to estimate the professional quality of life [Compassion Satisfaction (CS), Secondary Traumatization (ST) and burnout] using ProQOL-5 scale. Depression and Anxiety were estimated using PHQ-9 and GAD-7 scales respectively. Statistical analysis used: Association between the variables was found using Chi-square test. Results: Among the 318 respondents (170 males and 148 females), CS and ST levels were high in 77(24.2%), and 10(3.1%) respondents respectively. Severe depression and anxiety were among 36(11.3%) and 109(34.3%) respectively. Statistically significant association was found for Burnout (?2=55.671; OR=15.135; 95% CI=6.361-36.013 and ?2=57.518; OR=18.014; 95% CI=7.054-46.007) and ST (?2=56.701; OR=15.432; 95% CI=6.486-36.717 and ?2=26.281; OR=4.558; 95% CI=2.476-8.390) with both depression and anxiety (p<0.05). Conclusions: Doctors of Tamil Nadu, South India are challenged with adverse mental health outcomes during the COVID-19 pandemic with a significant association between the quality of life at work and psychological distress.